Immune thrombocytopenia in the newborn - Murat Yurdakök (Hygeia Press di Corridori Marinella, 2017)
The leading cause of moderate or severe thrombocytopenia in otherwise healthy appearing neonates is immune thrombocytopenia. Immune thrombocytopenia in the fetus or newborn may result from platelet alloantibodies against paternal antigens inherited by the fetus (alloimmune thrombocytopenia) or platelet autoantibodies in the mother with immune thrombocytopenic purpura (ITP). Only 10% of human platelet antigen (HPA)-1a negative mothers who are exposed to HPA-1a positive fetal platelets during pregnancy develop HPA-1a alloantibodies, and 30% of fetuses/neonates will develop thrombocytopenia and 20% of these cases being severe. The most serious complication of severe fetal and neonatal alloimmune thrombocytopenia (FNAIT) is intracranial hemorrhage (ICH), which is detected in 10-20% of affected fetuses/neonates, with most cases occurring antenatally. ICH leads to neurological sequelae in 20%, and deaths in 5-10% cases. There is no evidence-based optimal treatment strategy. Platelet antibody titration in maternal plasma is not helpful for decision-making. The best indicator for current pregnancy is the outcome of the previous pregnancy. The risk of recurrence among subsequent HPA-positive sibling is close to 100% where the previous sibling was affected with antenatal intracranial ICH. The risk of ICH becomes higher with more severe and earlier onset in each subsequent pregnancy. Serial platelet counts should be obtained for the first 5-7 days of delivery to keep the platelet counts higher than 30,000/µL without active bleeding and higher that 50,000-100,000/µL with active bleeding. Intravenous immunoglobulin (IVIG) is not alternative to platelet transfusions, since platelet counts don't rise before 24-48 h. In platelet- transfused patients, IVIG can be given to potentially prolong the survival of the incompatible platelets. ITP during pregnancy is not considered a serious risk of perinatal bleeding, but may cause a moderate thrombocytopenia in neonate. In mothers with ITP, the risk of thrombocytopenia is only 10%, with no more than 1% risk of in utero ICH.